Urbanization and Dialect Decline in Indonesia: A Study of Intergenerational Language Shift and Policy Gaps - Jala, Jusrianto; Idayanti; Kusuma, Sonya Ayu (Indonesian Scientific Publication, 2025)
Urbanization has reshaped Indonesia’s linguistic landscape, especially in major cities where Bahasa Indonesia (BI) increasingly replaces local dialects. This study examines how urbanization, generational change, and policy frameworks affect dialect use in urban Indonesia. Drawing on data from the 2020 Long Form Census, generational language use statistics, and comparative policy analysis, this research contrasts low usage urban provinces like Jakarta and Kepulauan Riau with dialect stronghold regions such as Bali and Yogyakarta. The methodology combines quantitative data analysis with qualitative insights, including census based trends in dialect use across generations and detailed case studies of local policy environments. Key findings reveal that urban centers with limited institutional support experience significant dialect erosion, especially among younger cohorts. In Jakarta, only 0.5% of residents use local dialects with neighbors, while Bali and Yogyakarta report over 85%. Generational data further demonstrate a steep decline in dialect usage, with Post Gen Z exhibiting the lowest rates. These results underscore that dialect decline is not a deterministic consequence of national language policy but is strongly mediated by regional planning, cultural engagement, and community agency. Regions with proactive policies like Bali’s Pergub 80/2018 have successfully maintained dialect vitality through curriculum inclusion and public media usage. In conclusion, urban dialect preservation requires an integrative policy framework that balances national cohesion with local linguistic rights. Digital media, youth engagement, and community led initiatives are essential to reversing intergenerational language loss. This study contributes to sociolinguistic literature by highlighting the critical role of local governance and intergenerational dynamics in shaping linguistic resilience.